2021
DOI: 10.3390/app11041787
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Development of In Vitro Human Respiratory Epithelium Using Collagen Type I Scaffold as a Potential Model for Future Tracheal Tissue Engineering

Abstract: Pathological conditions of the tracheal epithelium, such as postoperative injuries and chronic conditions, often compromise the functionality of the respiratory epithelium. Although replacement of the respiratory epithelium using various types of tracheal transplantation has been attempted, there is no predictable and dependable replacement method that holds for safe and practicable long-term use. Therefore, we used a tissue engineering approach for ex vivo regeneration of the respiratory epithelium (RE) const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Notably, natural-based materials are not only more sustainable, but they also have higher biocompatibility, improved biodegradability, and in general, little to no toxicity [ 233 ]. Furthermore, in the context of the circular economy and sustainability, collagen sources such as bovine hide off-cuts [ 75 ], pig skin [ 82 ], chicken skin and eggshells [ 66 , 68 ], sheep legs [ 234 ], and fish scales [ 235 ] can be obtained from food waste. Moving forward, there is a significant need for protocols considering green chemistry such as using and fabricating products that are biodegradable and non-toxic to the environment.…”
Section: Current Insights and Conclusionmentioning
confidence: 99%
“…Notably, natural-based materials are not only more sustainable, but they also have higher biocompatibility, improved biodegradability, and in general, little to no toxicity [ 233 ]. Furthermore, in the context of the circular economy and sustainability, collagen sources such as bovine hide off-cuts [ 75 ], pig skin [ 82 ], chicken skin and eggshells [ 66 , 68 ], sheep legs [ 234 ], and fish scales [ 235 ] can be obtained from food waste. Moving forward, there is a significant need for protocols considering green chemistry such as using and fabricating products that are biodegradable and non-toxic to the environment.…”
Section: Current Insights and Conclusionmentioning
confidence: 99%
“…Selection of nasal turbinate over trachea was due to the following reasons: (a) nasal turbinate is harvested via non-invasive methods as compared to tracheae, which is often collected via invasive methods (i.e., tracheotomy), and this causes further stenosis and structural damage to tracheae in the tissue donor [38], (b) nasal turbinate is more readily available as compared to tracheae and (c) since nasal turbinate can be available from an autologous source, as opposed to allogeneic RECs (in which the cell donor and recipient patient are different individuals), it does not elicit an immune reaction in the tissue recipient. The RECs were following an established protocol [10] by which the expression of CK14 and 18, MUC5AC and Ki67 [35] and immunocytochemical expression of markers acetyl β-tubulin, CK14, MUC5AC and Ki67 were proven [35,36]. It has been shown that knocking down CK14 results in reduced cell proliferation and delay in cell cycle progression [39].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and culture of respiratory epithelial and fibroblast cells was performed as previously described [10] with slight modification. Nasal turbinate specimens discarded during turbinectomy were collected under aseptic conditions from six patients.…”
Section: Respiratory Epithelial and Fibroblast Cell Isolation And Cul...mentioning
confidence: 99%
See 1 more Smart Citation
“…As the airways are continually exposed to foreign agents and infections, airborne toxicants can potentially translocate through an intact or compromised epithelial barrier, generating possible systemic effects [12,14,15]. The epithelial damage can even result in the loss of surface epithelial integrity and partial or total epithelium shedding [16,17]. Consequently, developing and validating in vitro models to assess the biological responses to disruptions of this first-line upper airway defense is critical [18][19][20].…”
Section: Introductionmentioning
confidence: 99%